Accessory Gene Regulator (agr) group polymorphisms in methicillin-resistant Staphylococcus aureus and its association with biofilm formation: Specific virulence factors of methicillin-resistant S. aureus - Omer, Sharmin A.; Ganjo, Aryan R.; Haji, Sayran H.; Smail, Sakar B. (Cellular and Molecular Biology, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the main causes of community- and hospital-acquired infections. The expression of virulence genes in S. aureus is arranged by regulators like the accessory gene regulator (agr). The present study aims to estimate phenotypic characteristics of S. aureus and investigate the occurrence of agr genes with their correlation to biofilm formation. In this study, 34 MRSA strains out of 100 S. aureus isolates were recovered in a variety of clinical samples. Phenotypic characterization and ability of biofilm formation were assessed. About 8(24%) of isolates were biofilm producers. The percentages of biofilm production among isolates were 3(37.5%), 2(25%), 3(37.5%) as strong, moderate, and weak, respectively. Furthermore, the resistance rates for all antibiotics were higher in biofilm producers and 76% of the isolates were staphyloxanthin producers, around 82% of the strains showed resistance to H2O2. Hemolytic activity was detected in 74% of the total isolates. The activity of the protease enzyme was 68%. The lipase enzyme was active in 79% of the tested S. aureus isolates. The majority of isolates were established to be agrI 84%, followed by agrII 53%, agrIII 32%, and 30% of the isolates have agr IV. Our study indicated that the majority of MRSA isolates were non-biofilm producers and the agr I is the most dominant type. Thus, agr I is not correlated with biofilm production.